Heterologous xylose isomerase pathway and evolutionary engineering improve xylose utilization in Saccharomyces cerevisiae - Qi, Xin; Zha, Jian; Liu, Gao-Gang; Zhang, Weiwen; Li, Bing-Zhi; Yuan, Ying-Jin (Frontiers in Microbiology, 2015)
Xylose utilization is one key issue for the bioconversion of lignocelluloses. It is promising approach to engineer heterologous pathway for xylose utilization in Saccharomyces cerevisiae. Here, we constructed xylose-fermenting yeast SyBE001 by combinatorial fine-tuning the expression of XylA and endogenous XKS1. Overexpression of genes RKI1, RPE1, TKL1 and TAL1 in the non-oxidative pentose phosphate pathway in SyBE002 accelerated xylose utilization by 19%. By repetitive adaptation, the xylose utilization rate increased to about 10 folds in strain SyBE003 evolved from SyBE002. Gene expression analysis identified variety of genes with significantly different expressions in pentose phosphate pathway, glycolysis and tricarboxylic acid cycle in SyBE003.